Improving Outcomes after Stroke: From Stroke Units to Mobile Stroke Units - Andrei V. Alexandrov (2022)
A proactive clinical approach to stroke care improved functional outcomes with implementation of specialized in-hospital stroke units, urgently delivered systemic thrombolysis, mechanical thrombectomy and most recently with mobile stroke units deployed in the field. An 18% absolute difference in outcomes as a shift across all modified Rankin Scale strata at 3 months in the recent Berlin study may not be explained by just 8.8% more patients treated within the golden hour for thrombolytic treatment from symptom onset. These findings parallel the findings in the largest controlled multi-center BEST-MSU trial (Benefits of Stroke Treatment Delivered Using a Mobile Stroke Unit) to date. A shortcoming in blinding of the investigators to the mode of transportation is similar to blinding to the endovascular treatment in PROBE (Prospective Randomized Open, Blinded End-Point) design used in thrombectomy trials. A faster access to stroke experts and brain imaging in the field for all patients suspect of stroke regardless symptom nature, severity, duration or resolution delivered by mobile stroke units is likely the reason for improved outcomes akin the impact observed in the initial multidisciplinary approach to in-hospital stroke units and reperfusion therapies delivery.